ACTUAL PROBLEMS OF BREEDING OF TABLE BEET - V. I. Burenin; T. M. Piskunova (Овощи России, 2018)
The popularity and wide spread of table beet due to its high nutritional qualities, content of biologically active substances (betaine and betanin), that make it a functional food. For Russia, characterized by a wide variety of soil and climatic conditions, varieties with high adaptability are necessary. Results of studying the genetic resources of table beet, including evaluation of cold resistance and non-bolting, monogermicity, productivity and quality of production are given in article. 56 accessions received by the collection of VIR from 17 countries are served as material for researches. Field study, evaluation of accessions during storage and analysis were carried out according to the methodological instructions of VIR. The evalution of the different origin beet accessions for their bolting showed that varieties from Sweden and Finland, as well as from the northwestern region of Russia, were the most bolting resistant. The variation in the level of bolting in domestic varieties of table beet was significant: from resistant to strongly bolting. The greatest tendency to bolting was observed in domestic varieties of southern origin. The harmfulness of the black root is especially significantly in the modern technology of beet cultivation, when sowing is carried out at a given density of standing plants. There are no varieties absolutely resistant to black root yet. Extra Early Egypt (USA), Banko (Sweden) and Fire Chief (USA), Detroit Supra and Detroit Bolivar (Netherlands), Kholodostoikaya 19 (Belarus), Bravo (Russia) were carried out from the studied accessions. The varieties of wide range, which annually provide a stable harvest in different soil and climatic conditions: Special Crosby (USA) and Forono (Denmark), Bordo 237 (Russia). For the Northern areas as well as inwinter and early spring sowings varieties Fiere Chief и Extra Early (USA), Banko and Adoptiv (Sweden), Podzimnyaya-474 Polyarnaya Ploskaya (Russia) are suitable.